On Cooling The Relevance Out - Gross, Matthias; Horta, Ana (Relevance and Irrelevance, 2018)
Given a general rise in dog pets in many societies, dog poop becomes an increasingly important issue. However, it appears as a subject less worthy of serious attention albeit it is known as a source of pollution and, when left on sidewalks and other public spaces, as a significant nuisance to human communities. Public authorities in many countries have considered it as a socially relevant issue by requiring owners to clean up after their dogs. For that to happen, however, dog walkers need to have incorporated the disposition to do so routinely, as a practical mastery enacted without conscious attention. In our research we observed a tendency to establish a respectful distance to others, including when something objectionable – but still with a socially ambiguous relevance, like not scooping dog poop – has been done. In such contexts, embodied dispositions to actively ignore dog waste may be used to save the face of those involved. We discuss several ways how nonknowledge emerges as a form of cooling its relevance out.